Portable moving images : a media history of storage formats - Cedeño Montaña, Ricardo, 1976- (De Gruyter, 2017)
"This media history explores a series of portable small cameras, playback devices, and storage units that expanded the production of film and video to the home. Covering several storage formats from the small gauge films of the 1900s, through the analogue videotapes of the 1970s, to the compression algorithms of the 2000s, this work inquires into the effects that the shrinkage of complex machines, media formats, and processing operations has had on the dissemination of moving images. Using a media archaeological approach to technical standards, the author provides a layered genealogy of portable storage formats for film, analogue video, and digitally encoded video. This book is a step forward in decoding the storage media formats of which usually only highly specialised technicians speak"--